2018 4th IEEE Conference on Network Softwarization and Workshops (NetSoft) 2018
DOI: 10.1109/netsoft.2018.8460125
|View full text |Cite
|
Sign up to set email alerts
|

Evolving SDN for Low-Power IoT Networks

Abstract: Software Defined Networking (SDN) offers a flexible and scalable architecture that abstracts decision making away from individual devices and provides a programmable network platform. Low-power wireless Internet of Things (IoT) networks, where multi-tenant and multi-application architectures require scalable and configurable solutions, are ideally placed to capitalize on this research. However, implementing a centralized SDN architecture within the constraints of a low-power wireless network faces considerable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…SDN is a well-defined approach and a promising solution for other networking areas. However, employing an SDN-based centralized architecture in the environment of a lowpower wireless IoT network introduces important challenges, such as the difficulty to control traffic, unreliability of links, network contention, and high associated overheads, which can significantly affect the performance of the network (Baddeley et al, 2018). This paper evaluates the overhead cost of SDN traffic network performance, delay, DER, and PDR.…”
Section: N Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…SDN is a well-defined approach and a promising solution for other networking areas. However, employing an SDN-based centralized architecture in the environment of a lowpower wireless IoT network introduces important challenges, such as the difficulty to control traffic, unreliability of links, network contention, and high associated overheads, which can significantly affect the performance of the network (Baddeley et al, 2018). This paper evaluates the overhead cost of SDN traffic network performance, delay, DER, and PDR.…”
Section: N Abstractmentioning
confidence: 99%
“…It was installed on a Lenovo-IdeaPad-Y510P Laptop with an Intel Core i7-4700MQ processor with 7.7 gigabytes of random access memory. In this environment, it was unnecessary to install the Contiki platform because it was included as part of the µSDN (Baddeley et al, 2018), a low overhead SDN stack, and embedded in the SDN controller for Contiki OS. However, it was necessary to install compilers such as the 20-bit mspgcc compiler (20bit) and the precompiled MSP430-GCC version 4.7.3 (msp430).…”
Section: Operating Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] From the network management viewpoint, SDN may enable traffic control and load balancing. As an example, in Baddeley et al, 31 it is shown that the SDN controller may steer traffic in noninterfered area, improving network performance. When it comes to resource utilization, the SDN approach allows viewing nodes as resource providers and to efficiently map the users' requests into the proper resources.…”
Section: Software-defined Iotmentioning
confidence: 99%
“…However, no resource management or QoS‐based network management is considered. An extension of the 6LoWPAN protocols stack was proposed to implement SDN, demonstrating performance improvement with respect to the Routing Protocol for Low Power and Lossy Networks (RPL)–based decentralized solution. Results are obtained via a platform emulating TI CC2420 devices and not using real devices as we do in our paper.…”
Section: Related Workmentioning
confidence: 99%